Bank risk evaluation through Z-score measure and its effect on financial health of the industry of transitional economy of Kazakhstan (Journal of Economic Research & Business Administration, 2020)
Studying the systematic risk of the banking industry, as a measure of the financial stability, is oneof the options to evaluate how strong is the overall industry’s standings against the systematic risk itself.There are number of studies in related areas for both developed and developing markets. This study isthe part of the overall examination of the banking industry performance for the developing transitionaleconomies. With the help of the risk evaluation through the measure of Z-score, we are trying to evaluatethe financial health of the institutions and as a whole the industry. This will let us explore the financialstandings and the performance of the particular market. The other point is that the examination coversthe post-financial crisis period with the certain macroeconomic fluctuations of the endogenous to theindustry problems such as devaluation in-between the study coverage timeframe. These impacting factorshelp us understand the effect of both external and internal shocks affecting the banking industry.The relationship between the financial stability and the overall profitability, as a risk and return relationshipwith the effects of external factors like crisis and internal macroeconomic shocks as devaluation isthe core point of the interest of this particular study. The findings suggest that the size of the bank playsimportant but negative role in the way bank behaves. It negatively affects the financial health of the bankindustry. Overall, the financial stability is very unstable; as the fluctuations of the Z-score over the periodof examination is significant, stating only that the transitional economy is very much vulnerable towardsboth internal and external risks.